PENANGGUHAN PEMBAYARAN PAJAK PPH DAN BPHTB SEHUBUNGAN DENGAN PENDAFTARAN TANAH SISTEMATIS LENGKAP BERDASARKAN PERALIHAN HAK JUAL BELI - Aldi Sagita Hasibuan; Sri Setyadji (Gapenas Publisher, 2023)
Complete systematic land registration is land registration carried out for the first-time issuing certificates. The implementation of complete systematic land registration must guarantee certainty and legal protection of land ownership. Therefore, to provide comfort to landowners and authorities of a land plot, legal land registration is very important for the community. accelerating land registration is a must. There is an important issue regarding the legal certainty of rights to land registration, namely the transfer of rights in relation to PPH and BPHTB taxes payable. Article 33 of Minister of Agrarian and Spatial Planning/Head of National Land Agency Regulation No. 6/2018 is legally weak. The regulation does not yet regulate the formulation and procedures for payment of income tax and BPHTB payable. because Article 90 of Law No. 28 of 2009 concerning Regional Taxes and Regional Retribution, tax is payable due to legal actions, namely the transfer of rights, which can be caused by buying and selling, and inheritance. Thus, strengthen the rules regarding PTSL in Government Regulations, by revising Permen No. 6 of 2018 and/or forming a separate PP regarding PTSL, which basically regulates the problems described above. The method used in this research method is conceptual approach The conceptual approach is carried out when the researcher does not depart from the existing legal rules. This is done because there is no or no legal rule for the problem at hand.